Promising diagnostic tools for endometriosis given the pathogenic role of genetic factors - G.A. Ikhtiyarova; M.Zh. Aslonova; Z.Sh. Kurbanova; D.M. Kalimatova (LCC «Medicine-Inform», 2021)
G.A. Ikhtiyarova1, M.Zh. Aslonova1, Z.Sh. Kurbanova1, D.M. Kalimatova2 1Bukhara State Medical Institute, Bukhara, Uzbekistan 2Pirogov Russian National Research Medical University, Moscow, Russian Federation This paper discusses promising diagnostic modalities for endometriosis considering current ideas about the role of genetic factors in the pathogenesis of this condition. The hypotheses on pathogenesis and modern diagnostic approaches are addressed. The authors uncover the issues of genetic predisposition to endometriosis. The inhibition of tumor suppressor genes (CDKN2B, CDKN2 A, and ARF) and the activation of genes of early (embryonic) development of the female reproductive system (HOXA, HOXB, WNT4) lead to endometrial metaplasia. As a result, endometrial cells gain the ability to proliferate. The role of microRNA in the impaired regulation of the methylation of various genes associated with endometriosis is described. These factors specifically affect the course and clinical manifestations of endometriosis. Certain key proteins involved in the pathogenesis of endometriosis and whose synthesis is controlled by microRNA may be regarded as the diagnostic markers of endometriosis. Their in-depth study will identify novel therapeutic targets and promote the development of new non-hormonal treatment approaches to endometriosis. Keywords: endometriosis, proliferation, endometrium, genes, polymorphism, diagnostic, epigenetics, microRNA. For citation: Ikhtiyarova G.A., Aslonova M.Zh., Kurbanova Z.Sh., Kalimatova D.M. Promising diagnostic tools for endometriosis given the pathogenic role of genetic factors. Russian Journal of Woman and Child Health. 2021;4(1):12-16. DOI: 10.32364/2618-8430-2021-4-1-12-16.